2020
DOI: 10.1096/fj.201901380rr
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA growth arrest‐specific transcript 5 alleviates renal fibrosis in diabetic nephropathy by downregulating matrix metalloproteinase 9 through recruitment of enhancer of zeste homolog 2

Abstract: Diabetic nephropathy (DN) is a frequently occurred microvascular complication associated with type I and type II diabetes mellitus. The participation of long noncoding RNAs (lncRNAs) in diabetes-related microvascular complications has been reported extensively. We attempted to unveil the possible regulatory mechanism of lncRNA growth arrest-specific transcript 5 (GAS5) and matrix metalloproteinase 9 (MMP9), an important inflammatory protein, in the progression of DN. A rat DN model was induced by streptozocin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…In lncRNA-GATA6-AS1, for example, FZD4 expression is reduced by recruiting EZH and H3K27me3 to the FZD4 promoter region [13]. Again, LncRNA GAS5 is known to downregulate MMP9 by recruiting EZH2 in the MMP9 promoter region [14]. Similarly, from our study, LINC01419 transcriptionally regulated target proliferation and migration-related genes by binding to EZH2.…”
Section: Agingsupporting
confidence: 66%
“…In lncRNA-GATA6-AS1, for example, FZD4 expression is reduced by recruiting EZH and H3K27me3 to the FZD4 promoter region [13]. Again, LncRNA GAS5 is known to downregulate MMP9 by recruiting EZH2 in the MMP9 promoter region [14]. Similarly, from our study, LINC01419 transcriptionally regulated target proliferation and migration-related genes by binding to EZH2.…”
Section: Agingsupporting
confidence: 66%
“…Increasing evidence have indicated lncRNAs' involvement in the pathogenesis of many diseases, including fibrosis [32][33][34]. Previous studies have showed that lncRNA PFAL contributed to the progression of pulmonary fibrosis [35].…”
Section: Agingmentioning
confidence: 99%
“…Enhancer of zeste homolog 2 (EZH2) is a histone H3 lysine 27 (H3K27)-specific methyltransferase, and EZH2-mediated H3K27me3 is a suppressive posttranslational modification ( McCabe et al, 2012 ). Zhang, Zhao & Zhu (2020) demonstrated that GAS5 recruits EZH2 to the matrix metalloproteinase 9 (MMP9) promoter region, thereby resulting in a subsequent downregulation of MMP9 expression, which relieves renal fibrosis in diabetic nephropathy rats. EZH2-mediated H3K27 hypermethylation at the cyclooxygenase-2 (COX-2) promoter results in the epigenetic silencing of COX-2, facilitating the fibrotic process in idiopathic pulmonary fibrosis (IPF) ( Coward et al, 2014 ; Mozzetta et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%